Nanocellular Polymers : From Microscale to Nanoscale - Leon, Judith Martin de; Garcia, Victoria Bernardo; Perez, Miguel Angel Rodriguez (Bostan: De Gruyter, 2024)
The book covers production, structure, properties and potential applications of nanocellular polymers fabricated by using foaming methods. These materials are porous materials with pore sizes in the nanometer range, processed as bulk or film materials, from a wide set of polymers. Reduction of pore size to the nanoscale drastically modifies important properties such as thermal conductivity, optical properties, mechanical properties and specific surface area among others providing improved properties and promising applications for these materials in automotive, aeronautic, renewable energies, construction, filtration or thermal insulation.
Keywords: Nanostructured materials; Polymeric foams; Polymers$1 (BNanostructures; Materials science; Nanotechnology